Retrospective Review of Immediate Restoration of Lordosis in Single-Level Minimally Invasive Transforaminal Lumbar Interbody Fusion: A Comparison of Static and Expandable Interbody Cages. Issue 7 (16th November 2020) - Vaishnav, Avani S; Saville, Philip; McAnany, Steven; Kirnaz, Sertac; Wipplinger, Christoph; Navarro-Ramirez, Rodrigo; Hartl, Roger; Yang, Jingyan; Gang, Catherine Himo; Qureshi, Sheeraz A
Graphical Abstract: